IMPLENTASI PEMBELAJARAN AQIDAH AKHLAQ DALAM PEMBENTUKAN KARAKTER RELIGIUS SISWA DI MTS MIFDA PRIMA KABUPATEN PROBOLINGGO - Sholehati; Muhammad, Devy Habibi (LPPM STAI Muhammadiyah Probolinggo, 2024)
This study aims to explore the implementation of Islamic Moral Education in shaping religious character among students at MTS Mifda Prima Probolinggo, as well as to identify the supporting and hindering factors, along with the outcomes of applying this educational approach at MTS Mifda Prima Probolinggo. The research was conducted at MTS Mifda Prima Probolinggo, involving both the Islamic moral education teachers and the students as research subjects and informants. The applied method in this research is qualitative descriptive, where data, both written and oral, regarding the research subjects, are detailed. Data collection is carried out through observation, interviews, and documentation. Data analysis is performed using the Miles and Huberman approach, involving data reduction, data display, and drawing conclusions. The research findings indicate that the implementation of Islamic Moral Education in shaping religious character among students at MTS Mifda Prima Probolinggo is carried out through exemplary and habituation methods. This includes incorporating pre-lesson prayers, communal prayers, participating in the Tahsinul Qur'an program, fostering commendable behavior, and showing respect to teachers and peers. The goal is to support the formation of religious values that can be applied in daily life and provide positive examples. Identified hindering factors involve inadequate time allocation and the behavior of students.